Uncovering Gatsby Curves - Pier-André Bouchard St-Amant; Jean-Denis Garon; Nicolas Marceau (Center for Economic Studies and ifo Institute (CESifo), 2020)
Empirical findings suggest a positive correlation between inequality and social immobility, a phenomenon coined the Gatsby curve. However, complete explanations of the phenomenon have not yet been proposed. This paper answers two questions: What are Gatsby curves? When do they exist? We build a theoretical environment in which parental investment and education improve the economic prospects of children. Gatsbian economies and Gatsby curves are formally defined, and we characterize the conditions under which they will arise. We show that an economy may go from being Gatsbian to non-Gatsbian. Finally, we show that the better network of relations of those with high-paying jobs may also generate a Gatsbian economy.
Keywords: D31; H52; J31; J62; 330; intergenerational mobility; income inequality; education